Computational Psychometrics Approach to Holistic Learning and Assessment Systems - von Davier, Alina A.; Deonovic, Benjamin; Yudelson, Michael; Polyak, Stephen T.; Woo, Ada (Frontiers in Education, 2019)
Learning and assessment systems have grown and taken shape to incorporate concepts from both models for assessment and models for learning. In this paper we argue that a third dimension is necessary. Not only is it important to understand what the capabilities of a learner are, and how to grow and expand these capabilities, but we must consider where the learner is headed; we need to consider models for navigation. This holistic perspective of learning and assessment systems is encapsulated in the extended learning and assessment system, a framework for conducting research. Fundamental to this framework is the role of computational psychometrics to facilitate the abstraction from raw data to conceptual models. We provide several examples of research projects and describe how they fit into the described framework.